Fast simulation of multi-dimensional wave problems by the sparse scheme of the method of fundamental solutions. (August 2016) - Lin, Ji; Chen, C.S.; Liu, Chein-Shan; Lu, Jun
Abstract: In this work, a meshless scheme is presented for the fast simulation of multi-dimensional wave problems. The present method is rather simple and straightforward. The Houbolt method is used to eliminate the time dependence of spatial variables. Then the original wave problem is converted into equivalent systems of modified Helmholtz equations. The sparse scheme of the method of fundamental solutions in combination with the localized method of approximate particular solutions is employed for efficient implementation of spatial variables. To demonstrate the effectiveness and simplicity of this new approach, three numerical examples have been assessed with excellent performance.